2022
DOI: 10.1021/acs.energyfuels.2c00242
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan/Polyacrylamide Green Gels for Water Control in High-Temperature Reservoirs

Abstract: The rheology of a gel system composed of polyacrylamide (PAM) and chitosan is studied under typical reservoir conditions. The impacts of the degree of chitosan deacetylation, temperature, and salinity on the gelation behavior are assessed. The said system was prepared under ambient conditions and matured for 24 h at altered temperatures ranging from 50 up to 125 °C. An optimum formulation has been identified considering the rheological response and the initial viscosity constraints. The increase in the degree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 37 publications
(70 reference statements)
0
7
0
Order By: Relevance
“…Recently, our team has verified using chitosan as a green crosslinker to replace the PEI crosslinker and produce a stable in-situ polymeric gel in high-temperature and low-acidity reservoirs [27]. Chitosan is made from chitin, which is the second-most prevalent polymer in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our team has verified using chitosan as a green crosslinker to replace the PEI crosslinker and produce a stable in-situ polymeric gel in high-temperature and low-acidity reservoirs [27]. Chitosan is made from chitin, which is the second-most prevalent polymer in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 13d illustrates the loss factor and complex viscosity estimation as a function of the angular frequency for three PPGs: Ag/PAMBA 25% , Ag/PAMBA 5% , and Ag/PAMBA 0.5% , following a 30 day aging period. The analysis of the loss factor in this section indicates whether the polymer exhibits solid-like or liquid-like behavior, 6 offering insights into the structural state after prolonged exposure to high-temperature and highsalinity conditions. The findings reveal that the PPGs have tan δ values ranging from 0.051 to 0.297.…”
Section: Effect Of Agingmentioning
confidence: 99%
“…These fluids form a cross-linked three-dimensional (3D) structure under specific conditions, blocking water flow and decreasing permeability. Various materials have been suggested and employed for in situ gels to seal formations completely or partially. Our research groups have reported on these gel formulations. …”
Section: Introductionmentioning
confidence: 99%
“…The performance of the gel for microfracture plugging is tested in microfluidic porous media. There are several reports in the literature on the preparation of polyacrylamide-based hydrogels using chitosan as a cross-linker. , Recently, Elaf et al a chitosan-grafted PAM gel cross-linked with different proportions of N, N -methylene bis­(acrylamide) (MBA). Increasing the MBA concentration improves the elastic modulus at the expense of the SR of the PPGs.…”
Section: Introductionmentioning
confidence: 99%